A Study on Hydrogen Peroxide Scavenging Activity and Ferric Reducing Ability of Simple Coumarins - N Prahadeesh; Maheswaran Sithambaresan; Umaramani Mathiventhan (Ital Publication, 2018)
Coumarin compounds are δ-lactones where α-pyrone ring is fused with benzene ring. Coumarins are widely distributed in the plant kingdom as well as they are very important in synthetic organic chemistry. Coumarins have great interest because of their abundance in nature and diverse pharmacological activities including antibacterial, antiviral, antipyretic, and anticoagulant, antioxidant, anti-inflammatory and anticancer. This study focused on synthesizing different simple Coumarins and studying their antioxidant activity. Four simple Coumarins (Coumarin (C1), 4-hydroxy coumarin (C2), 7-hydroxy coumarin (C3) and 7-hydoxy-4-methyl coumarin (C4)) were synthesized by using standard methods and were characterized by using UV, IR, 1H and 13C NMR spectra. Antioxidant activity of the simple Coumarins was studied by using standard FRAP assay and Hydrogen peroxide assay and expressed as FRAP value (mmol Fe2+/g) and IC50 value (mg/dm-3) respectively. Ascorbic acid was used as standard. All synthesized simple Coumarins showed both antioxidant activities. Hydroxyl Coumarins (C2, C3 and C4) showed higher activities in both cases than C1. Among the hydroxyl Coumarins C3 showed highest hydrogen peroxide scavenging activity and Ferric reducing capacity too. Antioxidant power of the tested simple Coumarins in decreasing order was C3, C2, C4 and C1 in both cases. But the hydrogen peroxide scavenging activity and Ferric reducing capacity of the all synthesized simple Coumarins were lower when compared to standard ascorbic acid.